EVALUATION OF in vitro AND in vivo MANAGEMENT STRATEGIES AGAINST STEM GALL OF CORIANDER CAUSED BY Protomyces macrosporus (Unger.) (Applied Biological Research, 2023)
The present study was aimed to evaluate the effect of different biocontrol  agents, botanicals and fungicides on crop yield and stem gall disease of  coriander (Coriandrum sativum L.), caused by Protomyces macrosporus Unger. The effectiveness of plant leaf extracts, fungicides and bioagents  were evaluated against the test fungus under in vitro conditions by using  poisoned food technique and further evaluated under field conditions for  disease managemenand crop yield improvement. Among the biocontrol  agents and botanicals evaluated, Pseudomonas fluorescens and datura leaf  extract were most effective in in inhibiting the pathogenic growth; whereas  amongst fungicides, metalaxyl + mancozeb @ 0.2% and copper  oxychloride @ 0.2% were significantly superior with 100% pathogenic  growth inhibition under in vitro conditions. Under field conditions, seed  treatment and foliar spray of metalaxyl + mancozeb and copper  oxychloride @ 0.2% proved most effective in managing the disease as well as improved crop yield (1493.06 and 1284.72 kg ha-1, respectively) in  comparison to the control (729.17 kg ha-1).
Keywords: Bioagents; botanicals; coriander; fungicide; stem gall